Sequential patterns of inflammatory events during developing and expressed skin late-phase reactions - Zweiman, Burton; Haralabatos, Irene C.; Pham, Ngoc-Chân; David, Mary; von Allmen, Carolyn (Journal of allergy and clinical immunology, 2000)
Background: Although there has been much study of the histologic features of the late-phase reactions (LPR) seen 6 to 24 hours after intradermal injection of allergens, much less is known about the events occurring during development of such LPR. Objective: Our purpose was to compare sequential gross and histologic inflammatory responses during developing skin LPR within 6 hours after challenge. Methods: Gross reactions were measured and biopsy specimens obtained at 20 minutes and 1, 2, and 6 hours after intradermal allergen (Ag) and buffer diluent control (B) injections in 7 atopic subjects with known immediate and LPR. Inflammatory cell responses were compared, as detected by immunohistochemistry in Ag and B sites. These findings were then compared with those at 24 hours. Results: Gross LPR evolved without a hiatus from the immediate wheal responses over the next 6 hours (P = .04 vs that in B sites) and then decreased by 24 hours. Prominent PMN accumulation started by 20 minutes, peaking at 1 hour (P < .01). Eosinophil accumulation was significant, starting at 1 hour (P < .001) and peaking at 6 hours (P < .001). Many eosinophils were activated (EG2+). T-cell accumulation started at 2 hours (P = .01) and was most prominent at 24 hours. The frequency of vessels expressing E-selectin increased at 1 hour (P < .005), correlating with the degree of local PMN accumulation. The frequency of vessels expressing vascular cell adhesion molecules started increasing at 6 hours (P = .02), well after eosinophil accumulation was prominent. Conclusions: Skin LPR is characterized by evolution of a gross indurated reaction from the immediate whealing response over the first 6 hours after intradermal Ag challenge, with an early accumulation of PMN and eosinophils, not directly attributable to lymphocyte entry or vascular cell adhesion molecule expression. Likely, multiple other factors may also play roles in the complex pathogenesis of LPR. (J Allergy Clin Immunol 2000;105:776-81.)